The Value of Private Schools: Evidence from Pakistan - Pedro Carneiro; Jishnu Das; Hugo Reis (Institute for the Study of Labor (IZA), 2016)
Using unique data from Pakistan we estimate a model of demand for differentiated products in 112 rural education markets with significant choice among public and private schools. Our model accounts for the endogeneity of school fees and the characteristics of students attending the school. As expected, central determinants of school choice are the distance to school, school fees, and the characteristics of peers. Families are willing to pay on average between 75% and 115% of the average annual private school fee for a 500 meter reduction in distance. In contrast, price elasticities are low: -0.5 for girls and -0.2 for boys. Both distance and price elasticities are consistent with other estimates in the literature, but at odds with a belief among policy makers that school fees deter enrollment and participation in private schooling. Using the estimates from the demand model we show that the existence of a low fee private school market is of great value for households in our sample, reaching about 25% to 100% of monthly per capita income for those choosing private schools. A voucher policy that reduces the fees of private schools to 0 (from an average annual fee of 13) increases private school enrollment by 7.5 percentage points for girls and 4.2 percentage points for boys. Our demand estimates and policy simulations, which account for key challenges specific to the schooling market, help situate ongoing debate around private schools within a larger framework of consumer choice and welfare.
Keywords: I20; I21; 330; education; school choice; Pakistan; characteristics model